2010
DOI: 10.1124/jpet.109.161497
|View full text |Cite
|
Sign up to set email alerts
|

GLP-2 Receptor Agonism Ameliorates Inflammation and Gastrointestinal Stasis in Murine Postoperative Ileus

Abstract: Glucagon-like peptide 2 (GLP-2) is a pleiotropic intestinotrophic hormone that we hypothesized could lessen gastrointestinal inflammation associated with postoperative ileus (POI). To test this idea, the prophylactic timing and dose of a long-acting variant of human GLP-2 linked to the Fc portion of murine immunoglobulin G (IgG) (GLP-2/IgG) was optimized in a murine model of POI. Surgically treated mice received a single dose of GLP-2/IgG, IgG isotype control, or phosphate-buffered saline 1 to 48 h before smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Exogenous GLP-2 helps heal mucosal injury in inflammatory models of chemical-induced colitis [9], NSAID-induced enteropathy [12], radiation-induced enteritis [28] and post-operative ileus [29], consistent with our results. The effects of endogenous GLP-2 on refeeding-induced intestinal adaptation model were studied using the GLP-2R antagonist GLP-2(3–33) or in GLP-2R knockout (KO) mice [3032].…”
Section: Discussionsupporting
confidence: 89%
“…Exogenous GLP-2 helps heal mucosal injury in inflammatory models of chemical-induced colitis [9], NSAID-induced enteropathy [12], radiation-induced enteritis [28] and post-operative ileus [29], consistent with our results. The effects of endogenous GLP-2 on refeeding-induced intestinal adaptation model were studied using the GLP-2R antagonist GLP-2(3–33) or in GLP-2R knockout (KO) mice [3032].…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, GLP-2R activation suppressed intestinal leukocyte infiltration and reduced the expression of genes regulating inflammation and barrier function in a murine model of surgical ileus (46) and in mice with experimental ileitis and colitis (40). Taken together, our findings establish the importance of the intestinal Glp2r for the regulation of host bacterial interactions and reveal a new role for GLP-2 in Paneth cell-derived enteric defense, and control of gut microbial communities.…”
Section: Consistent With Findings Of Enhanced Bacterial Translocationmentioning
confidence: 55%
“…The therapeutic potential of GLP-2 during intestinal inflammation has been previously examined. Several studies have shown that agonism of GLP-2R or inhibition of DPPIV (dipeptidyl peptidase-4), the proteolytic enzyme responsible for cleaving active GLP-2 into its inactive metabolite could reduce intestinal inflammation in different models of colitis and ileitis (2,10,31,40,41,49). Here, we assessed the potential efficacy of GLP-2 in reducing the severity of already established colitis.…”
Section: Discussionmentioning
confidence: 99%